(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The study aims to figure out the extent to which the commitment to the application of the International Financial Reporting Standards (IFRS) affects the results of the evaluation of banking performance, the study based on a key premise that the commitment of commercial banks to the application of international financial reporting standards positively affects the results of the evaluation of banking performance through the preparation of financial statements that are transparent, appropriate and comparable with other banks in all countries of the world, For the purpose of testing the hypothesis of the research and achieving its objectives, the deductive approach was used in the presentation, study and analysis of research variables in the theoretical aspect, the descriptive quantitative analytical approach and the comparative method were adopted in the practical aspect. The study reached a set of conclusions, the most important of which is that the results of the ratios and financial indicators based on the amounts extracted from the financial statements prepared in accordance with the International Financial Reporting Standards reflected positively on the evaluation of the performance of banks and led to improving the results of the performance evaluation of the bank and the process of comparison with the ratios of banks in other countries. The study also recommended the need to intensify efforts among the relevant authorities concerned with the process of applying international financial reporting standards in banks to increase focus and shed light on finding a unified mechanism for the application of standards and follow up on their proper application.